Economic analysis of groundwater contamination control in landfills of coalmine subsidence area. Issue 5 (February 2019) - Lin, Fei; Song, Dejun; Ren, Honglei; Wu, Dan; Lei, Zhengguo; Fang, Bihe; Tao, Yuezan
Abstract: There are a great number of irregular landfills in urban and rural areas, some of which have caused severe contamination in the soil environment. It has been of great practical significance to study the leachate migration with different control measures. From the perspective of technical feasibility and economic rationality, the coupling numerical model of groundwater seepage and solute transport is established and the migration processes of leachate are analyzed under different measures. In addition, the effectiveness of control measures and engineering cost are also comprehensively analyzed. The results show that the leachate has reached the downstream drinking wells which have caused the contamination risks after 15 years, while the combination of horizontal and vertical impervious measures can meet the design requirements for 30 years. Finally, the control effects and engineering cost of different measures can provide significant basic data for the seal design of irregular landfill site.